Faunal elements from the Deccan volcano‐sedimentary sequences of India: A reappraisal of biostratigraphic, palaeoecologic, and palaeobiogeographic aspects. (3rd December 2018) - Kapur, Vivesh V.; Khosla, Ashu
Abstract : The sedimentary sequences associated with the Deccan Flood Basalts, i.e., infratrappean and intertrappean deposits, are known to yield a diverse assemblage of fauna that includes foraminiferans, ostracods, molluscs, fishes, frogs, turtles, lizards, snakes, crocodiles, dinosaurs, and mammals. The existing literature debates the exact nature of origin, age, and duration of the Deccan volcanic activity; however, there is a general accord within the geosciences community that the Deccan Flood Basalts bestrode the Cretaceous–Palaeogene Boundary. Within the past few decades, the record of the biotic component (particularly faunal elements) reported from the Deccan‐volcano sedimentary sequences have grown both numerically and taxonomically. Constraining the age of the Deccan‐volcano sedimentary sequences has a direct bearing on the studies that discuss the origin, evolution of the biota in a palaeobiogeographic framework, and also in the context of changes in the palaeoenvironment and palaeoecology. Thus, it becomes important to reinforce the age, environment of the Deccan‐volcano sedimentary sequences, and the origin/affinity of the faunal elements recovered from within these sedimentary deposits. We here reappraise the biotic (with an emphasis on the fauna) evidence in a biostratigraphic, palaeoecologic, and palaeobiogeographic aspect.